2022
DOI: 10.1111/cup.14223
|View full text |Cite
|
Sign up to set email alerts
|

Penile extramammary Paget disease associated with urothelial carcinoma in situ: Case report and literature review

Abstract: Background: Extramammary Paget disease (EMPD) is an uncommon disease affecting older men and women. Clinically, it appears as a plaque lesion with an erythematous or leukoplakic background in regions with abundant apocrine glands such as female external genitalia, perineum, scrotum, and penis. Methods:We are presenting an 85-year-old patient with recurrent erythematous plaque lesions involving the penis and known to have urothelial carcinoma (UC) in situ of the bladder. A literature review of EMPD secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since the distal intergenic region does not contain the gene itself, nor the regulatory elements, transcription termination sites (TTS) and TSS of the genes, 23 we chose FABP5, the gene with the largest hypomethylation difference in the promoter region, for subsequent validation. Key pathogenic characteristics of Paget cells include the expression of CK7, CK20 and EMA, and immunohistochemistry and immunofluorescence identification of these proteins is typically regarded as a diagnostic technique for EMPD 8,24 . Using the newly collected three paired patient samples, we found that FABP5 was highly expressed in tumor tissues, and FABP5 was co‐located with CK7, CK20 and EMA that were reported as markers of EMPD 25 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the distal intergenic region does not contain the gene itself, nor the regulatory elements, transcription termination sites (TTS) and TSS of the genes, 23 we chose FABP5, the gene with the largest hypomethylation difference in the promoter region, for subsequent validation. Key pathogenic characteristics of Paget cells include the expression of CK7, CK20 and EMA, and immunohistochemistry and immunofluorescence identification of these proteins is typically regarded as a diagnostic technique for EMPD 8,24 . Using the newly collected three paired patient samples, we found that FABP5 was highly expressed in tumor tissues, and FABP5 was co‐located with CK7, CK20 and EMA that were reported as markers of EMPD 25 .…”
Section: Resultsmentioning
confidence: 92%
“…Key pathogenic characteristics of Paget cells include the expression of CK7, CK20 and EMA, and immunohistochemistry and immunofluorescence identification of these proteins is typically regarded as a diagnostic technique for EMPD. 8,24 Using the newly collected three paired patient samples, we found that FABP5 was highly expressed in tumor tissues, and FABP5 was co-located with CK7, CK20 and EMA that were reported as markers of EMPD. 25 In contrast, the expression of FABP5 was low in normal tissues of the same patient (Figure 2).…”
Section: High Expression Of Fabp5 In Empdmentioning
confidence: 97%
“…We did not consider these strictly to be metastases, since these cases are likely due to intraepithelial spread, not hematogenous. Nineteen other similar cases have been reported separately 11 …”
Section: Discussionmentioning
confidence: 91%